Kritik M. Mustafa Azami Terhadap Pemikiran Para Orientalis tentang Hadis Rasulullah - Kamaruddin Kamaruddin (IAIN Ponorogo, 2011)
One of controversial conclusions of the orientalists’ study on the hadis is that the authenticity of the hadis is actually not as high as the Muslims believed so far, because none of the traditions of the Prophet is truly authentic from the Prophet, especially the tradition relating to fiqh. The conclusion was in turn confirmed that it is very difficult to trust the hadis literature as a whole as an authentic record of all the sayings and practices of Prophet Muhammad. The conclusion has thus aroused reactions from the Muslim researchers, among others, a leading researcher on hadis, Muhammad Mustafa Azami. Azamifound that doubts expressed by the orientalists in the system of sanad are due to the their methodological errors in studying on sanad material studies, that is because they generally did not examine the chain of transmission based on the hadis main books, but on the books of fiqh and sirah wich were prepared in different way from the hadis book. Azami refuted the conclusions of the Orientalists and proved the authenticity of the hadis in several ways, included comparing the hadis from many students’ collections with their teachers’collections of hadis, comparing the statements of the scholars from different times, comparing with the of written documents, and comparing the hadis with verses of the Koran related.